Liberdades possíveis em espaços periféricos: escravidão e alforria no termo da vila de Arez (séculos xviii e xix) - Souza, Aldinízia de Medeiros (2013)
This paper discusses aspects of the slavery and emancipations in the village of Arez between the last quarter of the eighteenth century and the first decades of the nineteenth century. It seeks to identify the profile of the slaves and the emancipation possibilities in a peripheral region with few commercial activities, given that the most of the approaches about manumission consider towns and cities where the economic dynamics ware more pronounced, as places of higher possibilities of slaves working in diverse activities that allowed them to accumulate a reserve fund and thus buy their freedom. Therefore it was necessary to raise evidences of slavery in the case study, which was based on surveys of the eighteenth century, and the first decades of the nineteenth century and some population maps and civil records related to the early nineteenth century. The information about the manumission acts were analyzed based on writs of freedom registered in the village of Arez between 1774 and 1827 due to the absence of other documents about it. The registry books include all the documents of the Arez community; so, it was possible to observe what happened in rural localities, in the town, in the headquarters of the district and in the village of Goianinha. Based on information from the documents, it was possible to address some aspects of slavery like the predominant types of groups, the possible activities in which slaves were inserted and the profile of the freed slaves, the emancipation modes and, therefore, discuss the possible relations ship between the colonial space and manumissions and between masters and slaves